Skull Base Repair following Resection of Vestibular Schwannoma: A Systematic Review (Part 2: The Translabyrinthine Approach) - Starup-Hansen, Joachim; Williams, Simon C.; Valetopoulou, Alexandra; Khan, Danyal Z.; Horsfall, Hugo Layard; Moudgil-Joshi, Jigishaa; Burton, Oliver; Kanona, Hala; Saeed, Shakeel R.; Muirhead, William; Marcus, Hani J.; Grover, Patrick (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives Despite advances in skull base reconstruction techniques, cerebrospinal fluid (CSF) leaks remain a relatively common complication after translabyrinthine (TL) vestibular schwannoma (VS) surgery. We conducted a systematic review to synthesize the repair techniques and materials used in TL VS surgery to prevent CSF leaks.Design A systematic review of studies published since 2000 reporting techniques to prevent CSF leaks during adult TL VS surgery was conducted. A narrative synthesis of primary repair protocols was produced, and a taxonomy was established. Additionally, the advantages, disadvantages, and associated CSF leak rates of different repair protocols were extracted.Results All 43 studies were case series, and 39 were retrospective. Repair strategies included heterogeneous combinations of autografts, xenografts, and synthetic materials. A taxonomy was produced, classifying repairs into seven distinct stages, including approaches to the dura, middle ear cleft, air cells, TL bony defect, extra-cranial soft tissue, postoperative dressings, and CSF diversion. The median postoperative incidence of CSF leaks was 6% (interquartile range: 0–10%).Conclusions This systematic review reveals substantial inter-institutional heterogeneity in intraoperative strategies to prevent CSF leaks following TL VS surgery. However, comparing these techniques is challenging due to the multiple predictive factors for CSF leaks and their inconsistent reporting. We propose a taxonomy of seven stages to classify operative techniques and materials aimed at preventing CSF leaks. We recommend that future evaluations should adopt a prospective approach encompassing data collection strategies that considers all operative stages described by our taxonomy.
Keywords: vestibular schwannoma; CSF leak; skull base repair; neurosurgery; ear nose and throat; translabyrinthine approach